Study of the Malabot Tumpe Tradition in Banggai Regency as an Ethnopedagogical Implementation of Biology Material - St Syahirah; Siti Sriyati (Yayasan Keluarga Guru Mandiri, 2024)
The emancipated learning curriculum has the potential to bring significant positive changes in enhancing educational standards. Its implementation aims to instill a love for regional culture and local wisdom. Indonesia's rich cultural diversity and unique traditions offer vast opportunities for developing biology materials grounded in local wisdom. However, local wisdom in Indonesia has been scientifically underexplored, necessitating further research to facilitate its integration into educational activities. This literature review examines the ethnoscience of the Malabot Tumpe tradition and its implementation within the emancipated learning Curriculum. Using the PRISMA model, the study identified and screened 35 articles based on theoretical relevance. The findings highlight the potential of the Malabot Tumpe tradition as supporting material in high school learning, particularly in phases E and F, encompassing biodiversity, ecosystems, and motion systems. Additionally, the tradition can be integrated into the Pancasila student profile by fostering global diversity appreciation. The study emphasizes the connection between science and cultural values, particularly in promoting sustainable conservation efforts to protect the Maleo bird population. This highlights the importance of embedding local wisdom into education for cultural preservation and environmental sustainability. Further research on Indonesia’s local wisdom is encouraged to expand its scientific exploration and educational application.